The math and science teacher and the communication with the itc. - Méndez Coca, David; Méndez Coca, Miriam (Historia y Comunicación Social, 2014)
The integration the ict in education progress successfully exceeding the barriers of the lack and unsuitable training of math and science teachers and the lack of means in schools. The advance of technology and the proper application of this technology to the education allow a personalized teaching and an improvement of the motivation in the students and enrichment of the didactic practice.